PENGGUNAAN MEDIA SOSIALISASI PEMILIH PEMULA BERBASIS ADOBE FLASH DI KABUPATEN SINTANG - Hazizah Hazizah; Aloysius Meriang (IKIP PGRI Pontianak, 2020)
This study aims to determine: (1) adobe flash design for novice voter socialization, (2) the implementation of novice voter socialization using adobe flash, (3) interest in novice voters after using adobe flash, (4) critical attitude of novice voters to foster awareness and positive attitude towards the election after using adobe flash. This research is a research development. Data obtained from interviews, observations, questionnaires and documentation. The results showed that: (1) adobe flash design for novice voter socialization was carried out through the Borg and Gall stages, (2) the implementation of novice voter socialization using adobe flash was included in the very appropriate category, (3) interest of novice voters towards general elections after using adobe flash is included in the category of Good, and (4) Critical attitude of novice voters to foster awareness and positive attitude towards elections after using adobe flash into the category is very appropriate. Therefore, it is expected that the central KPU can develop socialization media that are easy to use, fun, do not cause boredom, can increase the interest of novice voters to participate in elections and make it easier to understand the concept of general elections